Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films